Harmony in Islamic Boarding Schools, a Multicultural Education Model Based on Local Wisdom - Fathurrozi (STIT Attaqwa, 2023)
This research aims to determine a multicultural education model based on local wisdom. The research method used in the title Harmony in Islamic Boarding Schools, Multicultural Education Model Based on Local Wisdom uses a qualitative method with an ethnographic approach. Data collection techniques in this research used observation and interviews. Meanwhile, researchers carried out data processing using Spradley data analysis techniques consisting of domain analysis, taxonomic analysis, componential analysis and cultural theme analysis. To test the validity or validity of the data, researchers used ethnographic thematic analysis techniques. The research resulted in the finding that the multicultural education model based on local wisdom consists of 1). Integration of multicultural values ​​in materials and learning. 2). Habituation of religious tolerance activities. 3). Cross-cultural community and 4). Integration of Local Wisdom in the Curriculum.